Explaining Momentum and Value Simultaneously - Li, Jun (Management Science, 2018)
This paper proposes a unified risk-based explanation for momentum profits and the value premium in a neoclassical investment-based model. Winner firms have higher short-term productivity and hence more negative exposures to the price of investment goods than loser firms as a result of greater investment plans. Value firms have lower long-term productivity and higher operating leverage and hence higher sensitivities to neutral productivity shocks than growth firms. The model reproduces the coexistence of momentum profits and the value premium, the failure of the unconditional capital asset pricing model, the predictability of momentum profits by market states, and the long-term reversal of momentum profits. Empirical tests confirm a negative price of risk for the shock to the relative price of investment goods. This paper was accepted by Neng Wang, finance.